Performance measurement using balance scorecard leading to strategy formulation: A case study in water company - Milana Milana; Eri Wirdianto; Alexie Herryandie Bronto Adi (invotek, 2021)
Organization goals could be achieved by translating vision and mission into strategy. The strategy should be carefully formulated to direct the operation plans to work in harmony to achieve the goal. This research aims to show how the strategy is formulated based on the performance measurement result. The performance indicators are generated using the Balanced Scorecard approach with its four perspectives; financial, customer, internal business process, and learning and growth. Once these indicators and their benchmarks are defined, performance measurement is carried out. The performance measurement result is then input into a Strength-Weakness-Opportunity-Threat (SWOT) matrix. This approach proved that it could help the company review its existing strategy achievements and competitive position. Furthermore, the SWOT analysis proposes some potential actions taken by the company, which fall on Offensive, Defensive, Adjust, and Survive strategies.